13.4: Effects of VHR on the Flicker of Advanced Super Dimension Switching(ADS) Liquid Crystal Display. (4th October 2019) - Xu, Zhiqiang; Peng, Kuanjun; Qin, Wei; Wang, Tieshi; Teng, Wanpeng; Liu, WeiXing; Zhang, Chunfang; Li, Xiaolong; Guo, Kai; Li, Shengnan; Yang, Jin
Abstract : In this paper a new method was established to quantitatively analyzed the effects of VHR on the flicker of ADS LCD for both flicker pattern and L127 pattern, we find that for L127 pattern the flicker is mainly related with VHR and obtain their exact relation.